2020
DOI: 10.5530/pj.2020.12.182
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Investigations and Pharmacognosy of Striga orobanchioides Benth

Abstract: Hence, the current study was done to delineate pharmacognosy of the stem of plant Striga Orobanchioides Benth (Scrophulariaceae). MATERIALS AND METHODS Chemicals and instruments Potassium hydroxide, hydrochloric acid, Phloroglucinol, glycerin and all other chemicals used in the study were of analytical grade. Rotary microtome was used for taking sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Before any crude drug can be included in an herbal pharmacopoeia, pharmacognostic parameters and standards must be established. 20 The plants' identity and quality were determined by macroscopic and microscopic investigation before other analyses because their morphological identification was lost after they were dried and pulverized. 21 The pharmacognosy studies showed that the macroscopic characters of Bawang Dayak are characterized by a single leaf in the form of a ribbon and green, and its tip and base are spiky with a flat edge.…”
Section: Pharmacognostic Studymentioning
confidence: 99%
“…Before any crude drug can be included in an herbal pharmacopoeia, pharmacognostic parameters and standards must be established. 20 The plants' identity and quality were determined by macroscopic and microscopic investigation before other analyses because their morphological identification was lost after they were dried and pulverized. 21 The pharmacognosy studies showed that the macroscopic characters of Bawang Dayak are characterized by a single leaf in the form of a ribbon and green, and its tip and base are spiky with a flat edge.…”
Section: Pharmacognostic Studymentioning
confidence: 99%